Genetic and nutritional factors affecting ovine milk production traits and milk fatty acid content in Chios sheep breed - Symeou, Simoni (Department of Agricultural Science, Biotechnology and Food Science, Faculty of Geotechnical Science and Environmental Managment, Cyprus University of Technology, 2021)
This thesis focuses on the nutritional and genetic factors affecting milk production traits and fatty acid (FA) content of milk in Chios sheep. Improvement of milk production traits or milk fat quality of this breed can increase the quantity and/or quality of Halloumi cheese produced in Cyprus while enriching this dairy product with beneficial for human health effects lipids. The first part of the study aimed to evaluate feeding olive cake silage (OCS), a well-preserved by-product of olive oil production, on the FA profile of ovine milk (Chapters 2 and 3). In Chapter 2, thirty purebred Chios ewes were assigned to three diet treatments receiving 0%, 7% and 14% of OCS (on diet DM) for four weeks and the lipid content of their milk was assessed in lyophilized samples with nuclear magnetic resonance (NMR) technique. Results indicated that feeding these low and high rates of OCS reduced overall the saturated FA (SFA), increasing the unsaturated FA (UFA) content by 26% and 41% and the monounsaturated FA (MUFA) content by 30% and 46%, in milk samples, respectively. Furthermore, the content of beneficial for human health lipids, such as the conjugated linoleic acid (CLA) isomers, increased also in supplemented groups. In Chapter 3, the possible changes in milk of Chios sheep and related Halloumi cheese lipids with OCS diet inclusion were investigated by using gas-chromatography mass-spectrometry (GCMS) analysis. Sixty Chios ewes assigned to three diet treatments receiving 0%, 10% and 20% of OCS on DM basis and the results showed that OCS inclusion linearly increased UFA, MUFA, PUFA, CLA and oleic acid content in both milk and Halloumi cheese lipids, reducing at the same time the overall atherogenicity and thrombogenicity indices for both dairy products. Overall, the above trials showed that OCS is an alternative feed that can be used to improve the FA profile of ovine milk and Halloumi cheese without adversely affecting the lactating performance of Chios sheep. In the second part of the study, the objective was the identification of single nucleotide polymorphisms (SNPs) in the ovine candidate genes ACAA2, DGAT1, SCD1, FASN, and LIPG and assess their association with milk productions traits and the FA content of Chios sheep breed (Chapters 4-6). In Chapter 4, the aim was to investigate the potential association between a SNP of the ACAA2 gene, a T to C substitution located in the 3’ untranslated region (UTR), and important milk production traits in two extended Chios sheep populations from multiple flocks in Cyprus (742 animals in total) and Greece (632 animals in total). Databases were created containing lactation records from purebred Chios ewes in mid-lactation over 7 successive years from 20 flocks in Greece and during 8 successive years from 5 flocks in Cyprus. The mixed model association analysis revealed significant association of the investigated SNP with milk yield and milk content. In particular, the SNP was associated to milk yield with no effects on milk fat percentage in both populations, while the Cypriot population was also associated with milk protein percentage, milk protein yield and fat yield. In Chapter 5, molecular characterization of the UTRs of ovine DGAT1 and SCD1 genes in Chios breed was performed to identify polymorphisms putatively affecting milk traits due to the significant regulatory roles of those regions in gene expression. Along with those, previously identified polymporphisms of ACAA2 and FASN genes were also tested in relation to their effects on milk fat content and FA profile of Chios sheep milk. For this study 429 purebred Chios ewes in mid-lactation, were used for the collection of three consecutive monthly milk samplings and mixed models were used to analyze the association of the genotypic data identified. The 3′ UTR of the DGAT1 gene and the 5′ and 3′UTRs of the SCD1 gene appeared to be monomorphic and thus did not allow further association with milk traits. However, the FASN g.14777C>T SNP on exon 31 was associated with C13:0 and the ACAA2 g.2982T>C SNP in the 3′UTR was associated with C9:0, C11:0, C12:1 cis-9, C13:0 and the ω6/ω3 index, while fat percentage was not affected by the identified SNPs. In Chapter 6, the molecular characterization of the coding regions and the partial UTRs of the LIPG gene of a purebred population of Chios ewes in Cyprus was undertaken. Seventeen SNPs were identified in total with three of the SNPs located in exonic regions encoded non-synonymous mutations (g134C>A: ProThr, g1181G>A: GluGly, g2639G>T: ValGly) and six of the SNPs were located in exon 10 (3' UTR), while the rest of the mutations were synonymous. Preliminary association analysis of the identified haplotypes with milk traits suggested no association with milk fat percentage, protein percentage or milk FA profile traits. Finally, the main findings of the present work regarding both the nutritional treatments tested and the genetic polymorphisms investigated in Chios sheep breed are discussed in the final chapter of the thesis (Chapter 7). OCS supplementation in sheep feeding can be used as a useful tool for improvement of milk and Halloumi cheese FA content, while the identified polymorphisms in ACAA2 and FASN genes could be incorporated in SNP chips used for genomic selection aiming at improving milk production traits and the milk FA content.
Keywords: Halloumi; Milk production; Milk fatty acid